Risk Perceptions and Psychological Effects During the Italian COVID-19 Emergency - Lanciano, Tiziana; Graziano, Giusi; Curci, Antonietta; Costadura, Silvia; Monaco, Alessia (Frontiers in Psychology, 2020)
The current study provides data about the immediate risk perceptions and psychological effects of the COVID-19 pandemic among Italian participants. A sample of 980 volunteers answered a web-based survey which aimed to investigate the many facets of risk perceptions connected to COVID-19 (health, work, institutional-economy, interpersonal and psychological), and risk-related variables such as perceived knowledge, news seeking, perceived control, perceived efficacy of containment measures, and affective states. Socio-demographic characteristics were also collected. Results showed that although levels of general concern are relatively high among Italians, risk perceptions are highest with regards to the institutional-economy and work, and lowest concerning health. COVID-19 has been also estimated to be the least likely cause of death. Cognitive and affective risk-related variables contributed to explain the several risk perception domains differently. COVID-19 perceived knowledge did not affect any risk perception while the perceived control decreased health risk likelihood. The other risk-related variables amplified risk perceptions: News seeking increased work and institutional-economy risk; perceived efficacy of containment measures increased almost all perceived risks; negative affective states of fear, anger and sadness increased health risk; anxiety increased health, interpersonal and psychological risks, and uncertainty increased work, institutional-economy, interpersonal and psychological risk perceptions. Finally, positive affective states increased health risk perception. Socio-psychological implications are discussed.